PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN (Studi Kasus Pada Karyawan Rumah Makan Ayam Goreng Nelongso Jl. Sigura-gura Barat No. 27 Kota Malang) - M. Yulianto; M. Mansur; Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACT This study aims to examine and analyze the Effect of Transformational Leadership, Motivation and Work Discipline on Employee Performance at Nelongso Fried Chicken Restaurant Jl. West Sigura-gura No. 27 Malang City either partially or simultaneously. In this study a population of 32 employees and all were taken as samples. Data collection through questionnaires. Data analysis in this study using SPSS version 16. The sampling technique uses quantitative methods. Data testing techniques used in this study include validity test, reliability test, classic assumption test, multiple linear regression analysis, and testing the research hypothesis. The results of the analysis show that partially and simultaneously Transformational Leadership, Motivation and Work Discipline have a positive and significant effect on the Employee Performance of Nelongso Fried Chicken Restaurant Jl. Sigura-gura No. 27 Malang City.Keywords: Transformational Leadership, Motivation, Work Discipline and Employee Performance.